A comparison of an opioid abuse screening tool and prescription drug monitoring data in the emergency department. (1st February 2016) - Weiner, Scott G.; Horton, Laura C.; Green, Traci C.; Butler, Stephen F.
Highlights: It can be difficult to detect substance use disorders in emergency department patients. This study compared scores on the SOAPP-R screening tool with PDMP data. The sensitivity of SOAPP-R for detecting high-risk PDMP criteria was low (54%). Negative predictive value was high, so it may be a useful screening tool in the ED. Abstract: Objectives: This study aimed to: (a) determine the percentage of ED patients receiving prescriptions for opioid pain medications that meet the criteria for "high-risk for abuse potential" on the Screener and Opioid Assessment for Patients with Pain (SOAPP ® -R), (b) determine the percentage of patients with high-risk behavior on the state prescription drug monitoring program (PDMP) database, (c) compare the SOAPP-R with data from the PDMP, and (d) determine psychometric properties of SOAPP-R for ED patients Methods: Convenience sample of ED patients who were being considered for discharge with a prescription for an opioid pain medication. Subjects completed SOAPP-R on an electronic tablet and PDMP data was obtained. Scores on SOAPP-R ≥18 were defined as "at-risk", and PDMP data showing both ≥4 opioid prescriptions and ≥4 providers in 12 months was considered the criterion standard for high-risk behavior. Results: 82 patients (88.2%) provided consent. 32.9% ( n  = 27) were determined to be "at-risk" (score ≥18) by SOAPP-R. 15.9% ( n  = 13) subjects met PDMP criteria and 53.9% ( n  = 7) of those had SOAPP-R scores ≥18 (sensitivity 54%, specificity 71%, positive predictive value 26%, negative predictive value 89%). The association of an at-risk SOAPP-R score and PDMP high-risk criteria was an adjusted odds ratio of 1.39 (95% confidence interval 0.73–3.68). Conclusions: In our population, about one-third of patients being considered for discharge with an opioid prescription scored "at-risk" on SOAPP-R and 15.9% met the PDMP high-risk criteria. The high negative predictive value of SOAPP-R indicates it may be a useful screening tool for the ED patient population.